2016
DOI: 10.1038/srep38012
|View full text |Cite|
|
Sign up to set email alerts
|

Association between dioxin and cancer incidence and mortality: a meta-analysis

Abstract: The objective of the present study was to systematically assess the association between dioxin/2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and cancer incidence and mortality. Systematic literature searches were conducted until July 2015 in Pubmed, Embase and Cochrane library to identify relevant studies. A random-effects model was applied to estimate the pooled odds ratio (OR), risk ratio (RR), standard incidence ratio (SIR) or standard mortality ratio (SMR) for cancer incidence or mortality. In addition, dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 90 publications
1
32
0
1
Order By: Relevance
“…Expression of RelB was also shown to be critical for survival of Hodgkin lymphoma (122). Interestingly, a recent meta-analysis found that exposure and increased blood levels of TCDD are significantly associated with the mortality caused by non-Hodgkin’s lymphoma (123). Furthermore, our previous reports strongly support the function of AhR to mediate an anti-apoptotic response in human lymphoma cells (124) and the vital role of RelB in AhR-mediated apoptotic resistance in human breast cancer cells (61, 66).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of RelB was also shown to be critical for survival of Hodgkin lymphoma (122). Interestingly, a recent meta-analysis found that exposure and increased blood levels of TCDD are significantly associated with the mortality caused by non-Hodgkin’s lymphoma (123). Furthermore, our previous reports strongly support the function of AhR to mediate an anti-apoptotic response in human lymphoma cells (124) and the vital role of RelB in AhR-mediated apoptotic resistance in human breast cancer cells (61, 66).…”
Section: Resultsmentioning
confidence: 99%
“…The emission of dioxins and dioxin-like compounds into the atmosphere is clearly higher than in other industries except for food manufacturing (wood product manufacturing, 302.8970 mg-TEQ/year vs food manufacturing, 741.4960mg-TEQ/year)(Ministry of Economy, 2018). There have been reports that the most toxic dioxin (2,3,7,8-tetrachlorodibenzo-p-dioxin:TCDD) is statistically associated with cancer mortality (pooled standard mortality ratio = 1.09, 95%CI = 1.01-1.19) (Xu et al, 2016). However, there are no relevant data regarding the relationship between ambient dioxin exposure and cancer development (Xu et al, 2016;Danjou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports that the most toxic dioxin (2,3,7,8-tetrachlorodibenzo-p-dioxin:TCDD) is statistically associated with cancer mortality (pooled standard mortality ratio = 1.09, 95%CI = 1.01-1.19) (Xu et al, 2016). However, there are no relevant data regarding the relationship between ambient dioxin exposure and cancer development (Xu et al, 2016;Danjou et al, 2019). As far as we know, a reduction in cancer risk, as shown in the present study has not been associated with wood products.…”
Section: Discussionmentioning
confidence: 99%
“…43 The tumorigenic potential of dioxins has been described in the literature, and TCDD is now classified as a human carcinogen by the International Agency for Research on Cancer (IARC) based on animal and human observational studies; in particular, non-Hodgkin lymphoma is particularly frequent. 44,45 However, this remains controversial as the evidences for a relationship between TCDD and human carcinogenesis are indirect. The 40-year follow-up of the Vietnam and Seveso populations did not conclude that TCDD exposure promotes an increase of cancer incidence.…”
Section: Discussionmentioning
confidence: 99%